A Prospective Validation of the Updated Movement Disorders Society Research Criteria for Prodromal Parkinson's Disease. Issue 10 (22nd June 2020) - Giagkou, Nikolaos; Maraki, Maria I.; Yannakoulia, Mary; Kosmidis, Mary H.; Dardiotis, Efthimios; Hadjigeorgiou, Georgios M.; Sakka, Paraskevi; Ntanasi, Eva; Anastasiou, Costas A.; Xiromerisiou, Georgia; Stefanis, Leonidas; Scarmeas, Nikolaos; et al.
ABSTRACT: Objective: The objective of this study was to validate the recently updated research criteria for prodromal Parkinson's disease (pPD) proposed by the International Parkinson's Disease and Movement Disorders Society. Methods: A total of 16 of 21 markers of pPD were ascertained in the Hellenic Longitudinal Investigation of Aging and Diet cohort composed of community‐dwelling individuals aged ≥65 years. The probability of pPD was calculated for 961 individuals without Parkinson's disease (PD) or dementia with Lewy bodies at baseline who were followed‐up for a median of 3 years. The ability of the criteria to predict conversion to PD/dementia with Lewy bodies was assessed by estimating their sensitivity and specificity, plotting receiver operating characteristics curves, and using logistic regression. These analyses were repeated using the original criteria. Results: No incident PD/dementia with Lewy bodies case had probable pPD at baseline (ie, ≥80% pPD probability). At cut‐offs of 10%, 30%, and 50% probability of pPD, the sensitivity and specificity of the criteria ranged from 4.5% to 27.3%, and 85.7% to 98.3% respectively. The area under the receiver operating characteristics curve was 0.691 (95% confidence intervals, 0.605–0.777). In logistic regression models, the criteria‐derived posttest odds of pPD were a significant predictor of conversion at follow‐up. The updated criteria performed similarly to the original but showed a slight increase in sensitivity. Conclusions: The new criteria demonstrated suboptimal sensitivity in our random sample of community‐dwelling individuals. The absence of specialized assessments with high likelihood ratios in our cohort could be hindering the demonstration of higher sensitivities. Such assessments should be a part of future validation attempts. © 2020 International Parkinson and Movement Disorder Society